Spectroscopic photoacoustic microscopic imaging during single spatial scan using broadband excitation light pulses with wavelength-dependent time delay - Takeshi Hirasawa; Kazuyoshi Tachi; Manami Miyashita; Shinpei Okawa; Toshihiro Kushibiki; Miya Ishihara (Photoacoustics, 2022)
In most multispectral optical-resolution photoacoustic microscopy (OR-PAM), spatial scanning is repeated for each excitation wavelength, which decreases throughput and causes motion artifacts during spectral processing. This study proposes a new spectroscopic OR-PAM technique to acquire information on the photoacoustic signal intensity and excitation wavelength from single spatial scans. The technique involves irradiating an imaging target with two broadband optical pulses with and without wavelength-dependent time delays. The excitation wavelength of the sample is then calculated by measuring the time delay between the photoacoustic signals generated by the two optical pulses. This technique is validated by measuring the excitation wavelengths of dyes in tubes. Furthermore, we demonstrate the three-dimensional spectroscopic OR-PAM of cells stained with suitable dyes. Although the tradeoff between excitation efficiency and excitation bandwidth must be adjusted based on the application, combining the proposed technique with fast spatial scanning methods can significantly contribute to recent OR-PAM applications, such as monitoring quick biological events and microscale tracking of moving materials.